Taking on the Persona of a Suicide Bomber: a Thought Experiment - Anne Speckhard; Beatrice Jacuch; Valentijn Vanrompay (Perspectives on Terrorism, 2012)
Nineteen university students experimented taking on the persona of an apprehended suicide bomber.  The role play explored the psychological mechanisms of dissociative phenomena, euphoria or a sense of empowerment contemplating suicide bombing; responses of imagined secondary traumatization; identification with the victim group; creation of fictive kin; choosing the (imagined) target; and their (imagined) moral reasoning.  Results were eerily similar to accounts of real (failed) suicide bombers. Subjects identified with secondary trauma and fictive kin; and reported revenge and justice seeking as motivators; dissociation, some having experiences of euphoria or empowerment when contemplating strapping on a bomb. Their moral reasoning was nearly identical with the one of suicide bombers, despite none of them being Muslim. Most imagined targeting children or civilians. This leads us to the tentative conclusion that psychological mechanisms underlying the contemplation to engage in suicide terrorism may be universal.